PENGARUH CAPITAL ADEQUACY RATIO, SOLVABILITAS, DAN UKURAN PERUSAHAAN TERHADAP RISIKO LIKUIDITAS PADA BANK UMUM SYARIAH DI INDONESIA - Dinda Maharani Jaiz; Rahmawati; Asriany (Jurnal Ilmiah Wahana Akuntansi, 2020)
This study aims to determine the effect of Capital Adequacy Ratio, solvability, and firm size on liquidity risk in Islamic banks in Indonesia. The population in this study were Islamic banks in Indonesia from 2014 to 2018. The research sample was 11 Islamic banks in Indonesia which were obtained by purposive sampling technique. The results showed the variable Capital Adequacy Ratio and solvability had a positive effect on liquidity risk in Islamic banks. Firm size does not have a positive effect on liquidity risk in Islamic banks.